Decomposing World Health Inequality - Menno Pradhan; David E. Sahn; Stephen D. Younger (Tinbergen Institute, 2001)
This study explores global inequality in health status, and decomposes it into within- andbetween-country inequality. We rely on standardized height indicators as our health indicator sincethey avoid the measurement pitfalls of more traditional measures of health such as morbidity,mortality and life expectancy. They also avoid measurement problems associated with usingincomes across time or place to compare welfare. Our calculation of world height inequalityindicates that in contrast with similar research on income inequality, within-country variation is thesource of most inequality, rather than the differences between countries.NBR>
Keywords: 330; health; inequality; Gesundheitsversorgung; Kinder; Lebensstandard; Sozialer Indikator; OECD-Staaten